Islamic Cognitive Behavior Therapy to increase self-efficacy, a study on a drug user student. - Djoko Nugroho; Listian Indriyani Achmad; Saiful Muktiali; Nenda Nenda; Sarwo Edy (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The problem of drug abuse is getting more complex day by day. The reasons for teenagers using drugs are curiosity or experimentation and seeking to have fun. Part of the appeal of using drugs is the assumption that drugs will increase self-efficacy (belief in one's own ability to complete a task), either directly or indirectly). Islamic Cognitive Behavior Therapy (ICBT) modifies behavior and changes cognitive processes when faced with temptation or when facing life's problems that they have to live through when they are free from drugs. This study used a qualitative approach with single case experimental designs. The research design used in this study is the A-B-A design. Phase A is where the client's condition is without treatment and the conditions experienced by the client are analyzed or the baseline phase. Phase B is the condition where the treatment/intervention ICBT is given, and the last phase A is the condition where the researcher sees the effect of the intervention that has been carried out on the client which is also called the follow-up phase. This research found that applying Islamic Cognitive restructuring therapy reduced negative thinking so that the client can prioritize quality life. The implementation of ICBT makes the client aware of its importance and improves life free from drug addiction.